Speech and language pathologists' perceptions and practises of communication partner training to support children's communication with high-tech speech generating devices. (18th August 2019) - Tegler, Helena; Pless, Mia; Blom Johansson, Monica; Sonnander, Karin
Abstract: Purpose: This study examined speech and language pathologists' (SLPs') perceptions and practices of communication partner training with high-tech speech generating devices (SGDs). Method: Fifteen SLPs were recruited throughout Sweden. The SLPs answered a study-specific questionnaire on communication partner training in relation to communication partners to children with severe cerebral palsy and intellectual disability. The results were analysed with descriptive statistics (closed-ended questions, responses on Likert scales) and content analysis (open-ended question) using ICF-CY. Results : Twelve SLPs completed the survey. Half had no or one training session with communication partners in the last year. One-third never used documents for goal-setting. Half seldom or never taught communication partner strategies. Three quarters only used verbal instructions. The main obstacles were environmental factors. Conclusions: This study contributes valuable knowledge about high-tech SGD interventions targeting communication partners. The high-tech SGD intervention may benefit from goal-setting, extended number of training sessions and a range of instructional approaches. Implications for Rehabilitation: Speech and language pathologist (SLPs) reported that children with severe cerebral palsy and intellectual disability (SSPI) can benefit from speech generating device (SGD) communication. Communication partner strategies and goal-setting supports the development of communication with SGD. SLPs seldom taught stakeholder communication partner strategies and instruments for goal-setting. Because stakeholders may vary in their way of learning SLPs need to use a variety of instructional approaches. SLPs used few instructional approaches, typically verbal information.